2006
DOI: 10.1111/j.1467-9280.2006.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development of Feature Binding in Visual Short-Term Memory

Abstract: The binding of object identity (color) and location in visual short-term memory (VSTM) was examined in 6.5- to 12.5-month-old infants (N= 144). Although we previously found that by age 6.5 months, infants can represent both color and location in VSTM, in the present study we observed that 6.5-month-old infants could not remember trivially simple color-location combinations across a 300-ms delay. However, 7.5-month-old infants could bind color and location as effectively as 12.5-month-old infants. Control condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
139
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(162 citation statements)
references
References 36 publications
21
139
2
Order By: Relevance
“…The modified version of the change detection task presented here allowed younger children to complete a task that had previously been too challenging; however, the capacity estimates it yielded do not reach 3 or 4 items until between 5 and 7 years of age, much later than the 10 months suggested by Ross-Sheehy and colleagues (or possibly 7.5 months, as in Oakes et al, 2006). Thus, it seems that the difficulty with the adult change detection task is not the explanation of the conflicting findings by Ross-Sheehy and colleagues and Riggs et al (2006).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The modified version of the change detection task presented here allowed younger children to complete a task that had previously been too challenging; however, the capacity estimates it yielded do not reach 3 or 4 items until between 5 and 7 years of age, much later than the 10 months suggested by Ross-Sheehy and colleagues (or possibly 7.5 months, as in Oakes et al, 2006). Thus, it seems that the difficulty with the adult change detection task is not the explanation of the conflicting findings by Ross-Sheehy and colleagues and Riggs et al (2006).…”
Section: Discussionmentioning
confidence: 91%
“…First, Oakes, Ross-Sheehy, and Luck (2006) showed that the ability to bind colors to locations in the preferential looking task coincided developmentally with the increase in capacity from 1 to 2 or more items at 7.5 months of age. As described above, Oakes et al (2009) showed that young infants did not prefer the changing stream at a set size of 3 even when all 3 items in the display changed with every blink.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence in support of such a distinction comes from behavioral studies that demonstrated illusory conjunctions of color and form, but not of conjunctions within the form domain in normal observers (Cohen and Feintuch, 2002); intact binding of form features, but not color-form conjunctions in Balint's patients (Friedman-Hill et al, 1995;Humphreys, 2001;Humphreys et al, 2000); and a developmentally later onset of successful binding of color-form compared to within-form conjunctions in young children (Oakes et al, 2006). Importantly, patients with posterior parietal lesions showed deficits in conjoining color, size, and form features, but were unimpaired in search for form conjunctions in visual search (Humphreys et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Others, however, suggested that a third area, probably in the posterior, superior parietal cortex, needs to be activated that binds both motion and shape processing areas (Zeki, 2001). This (temporary) binding between shape and motion may be related to attention or spatial processing, and which may have a different developmental time course (Oakes et al, 2006;Rentschler et al, 2004;Ross-Sheehy et al, 2003). Thus, it remains unknown to what extend neural development of SFM processing depends on both the development of motion processing related areas and areas that are not directly related to shape or motion processing.…”
Section: Introductionmentioning
confidence: 99%